Pengaruh Formulasi Jenis Telur serta Frekuensi Penyiraman Pupuk PSB terhadap Pertumbuhan dan Produksi Bayam Brazil (Alternanthera sissoo) - Robith Fathurrohman Musyafa'ali; Umi Barokah (Politeknik Negeri Lampung, 2026)
Brazilian spinach (Alternanthera sissoo) is a leafy vegetable with considerable potential for cultivation in urban farming systems. The effectiveness of Photosynthetic Bacteria (PSB) fertilizer is presumed to be influenced by the type of egg used as the fermentation substrate and the frequency of its application. This study aimed to evaluate the effects of egg type and PSB fertilizer application frequency on the growth and yield of Brazilian spinach. The experiment was conducted from February to March 2026 in the greenhouse of the Faculty of Agriculture and Animal Science, Universitas Ma’arif Nahdlatul Ulama Kebumen, using a two-factor Completely Randomized Design (CRD) with four replications. The first factor was the type of egg used as the fermentation substrate, while the second factor was the frequency of PSB fertilizer application. Data were analyzed using two-way analysis of variance (Two-Way ANOVA), followed by Duncan's Multiple Range Test (DMRT) at the 5% significance level. The results showed that, individually, egg type and PSB fertilizer application frequency had no significant effects on plant height, number of leaves, root length, fresh weight, or dry weight. However, the interaction between the two factors significantly affected stem diameter increment. The combination of PSB produced using chicken eggs and applied every six days resulted in the greatest stem diameter increment, reaching 0.1250 mm. These findings indicate that the interaction between egg type and PSB application frequency has the potential to influence stem growth in Brazilian spinach.